Material memories of travel: the albums of a Victorian naval surgeon. (July 2020) - Driver, Felix
Abstract: This paper considers the visual archives of maritime scientific exploration, from coastal sketches to ethnographic observation. It focuses on seven albums of John Linton Palmer, a British naval surgeon who served in the Pacific in the 1850s and 1860s, which are today part of the collections of the Royal Geographical Society (with the Institute of British Geographers). Through their drawing, recording and collecting, naval surgeons like Linton Palmer played a significant role in the development of natural history and ethnography during the nineteenth century. The paper discusses the historical significance and potential contemporary uses of the Linton Palmer albums in the context of three forms of memory-making: firstly, the documentation of topographic, antiquarian, ethnographic, microscopic and other field observations by means of drawing; secondly, the assembling of such materials into personalised albums, part of a distinctive nineteenth-century naval tradition by which the experience of travel was re-collected (in the case of Linton Palmer within the scientific culture of late-Victorian Liverpool); and thirdly, the contemporary uses of such forms of visual heritage in a variety of contexts from family history to Indigenous land claims. Highlights: Emphasises the importance of the visual archives of travel and exploration. Explores the signficance of memory for the formation and use of albums of drawings. Presents a study of seven remarkable albums assembled by a Victorian naval surgeon. Discusses the role of drawings in late-nineteenth century scientific culture. Contextualises visual archives in local, national and imperial histories.